454 Obesity does not modify the effect of 4 months of CPAP on leptin or adiponectin. (3rd May 2021) - Pak, Victoria; Maislin, David; Keenan, Brendan; Townsend, Raymond; Benediktsdottir, Bryndis; Guo, Xiaofeng; Pack, Allan; Gislason, Thorarinn; Kuna, Samuel
Abstract: Introduction: Leptin and adiponectin are cytokines produced by adipocytes. Leptin is involved in the pathogenesis of obesity and adiponectin is cardioprotective. Previous studies in adults with obstructive sleep apnea (OSA) assessing the effect of continuous positive airway pressure (CPAP) on these cytokines are conflicting, and whether obesity modifies the effect remains unknown. We examined the baseline and follow up levels of changes in plasma leptin and adiponectin following 4 months of CPAP treatment among obese (BMI>30) and non-obese (BMI≤30) participants. Methods: We evaluated 221 adults (84.6% males) in the Penn Icelandic Sleep Apnea (PISA) Study, with mean (±SD) body mass index (BMI) 31.7±4.9 kg/m2 and apnea-hypopnea index (AHI) 35.7±15.6 events/hour. Associations between changes in natural log of the biomarkers in obese and non-obese participants were evaluated, controlling for a priori baseline covariates of age, baseline BMI, race, sex, site, and current smoking status. Results: The mean proportional change (from baseline to follow-up) in log-transformed adiponectin and leptin in CPAP adherent participants was not significantly different between BMI groups. The baseline to follow up change in leptin post-CPAP was 1.01 (95% CI 0.95–1.08) in obese participants and 1.05 (95% CI 0.96–1.14) in non-obese participants. For adiponectin, the change post-CPAP was 1.04 (95% CI 0.95–1.15) in obese participants and 1.08 (95% CI 0.96–1.22) in non-obese participants. Conclusion: CPAP treatment did not have an impact on leptin or adiponectin levels. We also find no evidence for obesity modifying the effect of four months of CPAP on leptin or adiponectin. Support (if any): 1P01-1HL094307